Membangun Kemandirian Siswa Tunagrahita melalui Pembelajaran Pendidikan Agama Islam (PAI) di SLB Wiyata Dharma Kota Metro - Saefullah, Muhamad; Wijayati, Mufliha (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2024)
This article examines several significant insights derived from best practices in teaching Islamic Education (PAI), which facilitate the cultivation of independence among students with intellectual disabilities. The research presented herein is the culmination of observations made during the modification of the Islamic Education learning process to accommodate the needs and skills of students with intellectual disabilities. The data for this study is corroborated through interviews and documentation. This paper posits that Islamic Education can serve as a viable pedagogical approach and habituation method for nurturing independence among intellectually challenged students for two primary reasons. Firstly, Islamic Education serves to instill independence in students across various domains including religious practices, moral conduct, social interactions, and essential activities in their daily lives. Secondly, despite the inherent limitations faced by intellectually disabled students, there exists untapped potential that can be harnessed and developed. This transformation of skills and capabilities among intellectually challenged students towards fostering independence can be effectively facilitated through Islamic Education instruction. Moreover, the positive outcomes resulting from Islamic Education instruction are reflected in intellectually disabled students attaining a sense of autonomy and self-sufficiency. This article further elucidates on the treatment methods and skills development, alongside habitual patterns, within three dimensions of Islamic Education instruction, such as Quranic recitation, theological understanding encompassing beliefs (Aqidah), purification rituals, ablution, fundamental knowledge of prayer rituals, performance of midday and forenoon prayers (Ibadah), cultivation of kindness, and avoidance of reprehensible behaviors (Akhlak). These efforts are aimed at nurturing independence and enabling intellectually disabled students to derive practical benefits according to their individual capacities.